Punggawa-Sawi: Financial System of Underprivileged Fishermen in South Sulawesi - Jafar, Muhammad Kamil; Tubagus, Sofyan; Anggol, Abdurrahman (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2024)
The Punggawa-Sawi system represents a patron-client relationship mechanism that dominates the traditional fisheries sector in South Sulawesi. This relationship is characterized by the dominance of the punggawa as the primary capital provider and the dependency of the sawi as workers, creating a complex socio-economic dynamic. This study aims to deeply explore the practices of the Punggawa-Sawi system and its impact on the welfare of underprivileged fishermen. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that the system fosters structural dependency, reinforcing the dominant position of the punggawa. Fishermen face injustices in the distribution of catch profits, burdensome debts, and limited access to formal financial institutions. Nonetheless, there are reform potentials through strengthening fishermen cooperatives, financial education, and the utilization of financial technology. These reforms require collaboration among the government, private sector, and fishing communities to create a more inclusive and equitable system. This study reinforces patron-client theory and offers new perspectives on addressing the challenges faced by underprivileged fishermen. By leveraging community-based and technological approaches, the Punggawa-Sawi system can be reformed to improve fishermen's welfare and foster economic sustainability in the fisheries sector.